SURVEI TINGKAT KEBUGARAN JASMANI PEMAIN SEPAK BOLA USIA 13-15 TAHUN DI AREMA FOOTBALL ACADEMY KOTA MALANG - Tsawri Afandy; Olivia Andiana; Rias Gesang Kinanti (Jurnal Sport Science, 2016)
Abstract: The purpose of this study was to determine the level of physical fitness of soccer players aged 13-15 years in Arema Football Academy by measuring the ability of a test cardiovascular endurance using rockport. This research uses descriptive quantitative research with survey techniques. Rockport test results in 33 subjects showed that there were 13 subjects obtaining the category of "Enough" with the greatest percentage of 39.4%, 10 subjects who obtained the category of "Less" with the second-worst percentage of 30.3%, 7 subjects acquire the category of "Good "with a percentage of 21.2%, 3 subjects acquire the category of" less nice "with a percentage of 9.1% and none of the subjects that received the category of" very Good "with a percentage of 0%. Based on the results the percentage can be concluded that the level of physical fitness of soccer players aged 13-15 years in Arema Football Academy dominant in the category "Enough".Keywords: physical fitness, Arema Football Academy.